"Shelter from the storm?" - Danish flexicurity and the crisis - Per Madsen (IZA Journal of European Labor Studies, 2013)
The Danish model won fame for its performance during the 1990s and the beginning of the 2000-years and took a position as a model for the European Employment Strategy and a much cited example of a real life flexicurity model. Like most other European countries Denmark has now fallen into a deep economic crisis. This has created debates about the ability of the Danish model to sustain external chocks. Some have further argued that Danish employment will be more vulnerable to economic downturns due to the low level of employment protection legislation (EPL). These issues are in the focus of the present article, which describes the reactions of the Danish employment system to the economic crisis and the relationship between the political responses to the crisis and some main institutional characteristics of the Danish labour market model.
Keywords: E32; J68; J08; 330; Flexicurity; Labour market institutions; Crisis; Unemployment